Ionic detox bathtub / Aqilah Mohd Shahari...[et al.] - Mohd Shahari, Aqilah; Muhamad Lokman Al- Hakim, Nur Farhana; Mohd Nazan, Mohamad Luqman Hakim; Mat, Nur Faidatul Nadhirah (2018)
By visiting Medina salon and spa company as study research, we were discovered the improvements that may lead the business keep updated as the other spa company. We were focused to spa because there are a lot of products services lacks in their company. So that, we were suggested our product development to their company for upgrade the standard as a spa company. We were suggested ionic detox bath tub as product development. This product was inspired by the combination of aroma therapy bath tub and also modern ionic detox foot. By taking these two elements, we considered its will save the electricity and time of people who are willing to get this product services. We are taking this effort to introduce this product as this company is not readily yet have the services. So, we were taking this opportunity to recognize our product for them and decide to commercialize the product. As figure out the study by interviewing the manager of the company, we found the target market of the services. This business was introduced to all range of the people, people in rehab and included career-driven women. These products were applied in Medina company in two or three units. These products also provided in maintenance by replacing the rubber blockage used during detox session. The estimated costs that we decided when get some information in internet and getting the comparison with the existing machinery is RM 180. The cost was estimated and decided in range as we found each existing product in market like ionic detox foot bath and therapy bath tub were higher than our innovation products. This will gives an opportunity to our customers saving their money to our product services.